Pipeline Modeling using UAV LiDAR Technology - Himawan, Iwan Qodar; Fitri, Listiyo; Widjajanti, Nurrohmat; Azizi, Iqbal Hanun (Departemen Teknik Geomatika ITS, 2024)
Pipelines play an important role in operations in energy supply companies, whether geothermal, gas, or petroleum. Pipeline damage, such as corrosion, dents, and leaks caused by natural or human factors, must be detected. Problems with pipeline assets will indirectly impact high production prices. Pipeline asset mapping must be carried out precisely, quickly, and quietly, considering that the existence of pipelines often causes social unrest. This research analyzed the capabilities of UAV LiDAR for mapping pipelines and support in a three km-long pipeline area. The study concluded that UAV LiDAR can map the position of the pipeline, its position to the ground, the position of the support, and the height of the support on a pipeline network with a diameter of 1 m. This capability applies not only to segments in open areas but also to those covered by vegetation. When orthophoto cannot display the pipeline's existence, the LiDAR point cloud can identify it. This main pipeline, which has a 1 m diameter, 3-D mesh, and 3-D models, can also be formed well. The accuracy of the resulting map is 11.5 cm at a confidence level of 90%. The length of time required from preparation to the presentation of the pipeline longitudinal profile map is eight calendar days with ten manpower.